Technological Pedagogical Skills for Teaching Technical Subject in School - Masek , Alias; Suhadi , Nurulain; Sidek , Hazwani; Ismail , Affero (Online Journal for TVET Practitioners, 2019)
Teaching in the 21st century entails the application of latest educational technology; it requires significantly different pedagogical skills compared with teaching in a traditional classroom using the whiteboard (chalk and talk). However, teachers’ pedagogical skills in using educational technology and its alignment to learning content have yet to be determined. In addition, the characteristics of the 21st century students have changed in terms of focus, motivation, and intelligence in learning. Therefore, this study was conducted to determine the 21stcentury pedagogical skills of teachers in using the recent educational technology. A survey was conducted using questionnaires that involved 282 teachers from the primary schools in the South-west of Johor, Malaysia (i.e. Batu Pahat, Kluang and Pontian). Data were analysed using mean, standard deviation and percentage in order to interpret the data. This is the result: the teachers have demonstrated a high level of skills in a total of 15 constructs of pedagogical skills in the 21st century teaching and learning using technology. The highest mean of pedagogical skills constructs includes improving students’ thinking, adapting material, and evaluating information. The implication is that, teachers should continually update their pedagogical skills for teaching and learning in the 21st century, in order to support students’ learning and impart knowledge effectively; such efforts are necessary to counter students’ declining interest and motivation, especially for the theoretical part of technical subjects in the school.